Kontribusi Islam Terhadap Peradaban Barat Islamic Contribution To Western Civilization - Abdul Pandi; Bahaking Rama; Muhammad Yahdi (Jurnal Studi Islam Lintas Negara (Journal of Cross-Border Islamic Studies), 2023)
Researchers are interested in researching this in order to find out: The Contribution of Islam to Western Civilization. This study aims to determine the Contribution of Islam to Western Civilization. The results of this study indicate that Islamic civilization in the West, the history of the development of Islam, experienced ups and downs and periodization, which Harun Nasution divided into five periods, namely: (1) Classical (2) Disintegration (3) Middle Ages (4) Three Great Kingdoms and (5) Modern - now. So that Islam came only to experience changes after Islamic scholastic thought entered the Western world as recognized by K.Bon that the changes that occurred in the West were due to the contributions of the Muslims, so that Christian Europe applauded its savagery. The arrival of Islam is a revolution that can reverse the flow of cultural waves towards a new world, which can place human values, freedom and safety. The Contribution of Islam to the Western World, The development of the Western world to this day, many contributions of Islamic intellectuals who developed in the classical period. There are several things that are most prominent in the contribution of Islam to Western civilization, namely: Natural Sciences Include: Astronomy, Mathematics, Chemistry and Medicine, Philosophy, Literature.